Pinwheel-Shaped Titanium Plates Should Be Fixed to the Skull Using All Screw Holes to Protect the Plates from Being Bent. (19th August 2019) - Yamada, Shoko Merrit; Gorai, Katsuya; Gonda, Koichi
Abstract : Introduction . In cranioplasty, pinwheel-shaped titanium mini plates are frequently used to cover bone defects produced by burr holes, and it is common to insert screws through only a few of the holes in cranial flap fixation. Presentation of Case . A 69-year-old man who had undergone clipping surgery for subarachnoid hemorrhage 16 years previously visited our clinic because a titanium plate had penetrated his scalp one month after he was hit on the head by a wall cabinet. Imaging studies revealed that part of the titanium plate had bent outwards and penetrated the skin. The plate was surgically removed, a relief skin incision was made 6 cm posterior to the skin defect to suture the defected portion without causing tension, and a skin graft was applied to the relief skin incision portion. Two months after the maneuver, the skin graft had been successfully incorporated without infection. Discussion . Even after the subcutaneous and the cutaneous tissue have completely covered the pinwheel-shaped titanium mini plate, an edge without screw fixation can be easily bent by a hard blow to the overlying scalp. We recommend fixation of pinwheel-shaped titanium plates used in cranioplasty through all screw holes to protect against the plate being bent.